(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s corporate world, many companies and organization are increasingly focusing on human capital as a competitive advantage in rapidly changing environment. Many successful companies realize that their employees are their greatest asset. Therefore, companies are increasingly investing in educating their own employees so that they can grow and change within the company and make it more profitable. The range of training opportunities varies considerable from company to company so, when researching potential employers, it is important for job seekers who care about this to investigate the level and type of training provided to employees. After employees have been selected for various positions in an organization, training them for specific tasks to which they have been assigned assumes greater importance. This study suggests the organization to implement more modern training methodologies, then to provide practical training to the employees and to provide specific learning assignments or projects for participants to improve on their competency gap.